Chemical and engineering thermodynamics - Sandler, Stanley I., 1940- (New York : John Wiley, 1999)
In this third edition, you'll find a modern approach to applied thermodynamics. The material is presented in sufficient detail to provide a solid understanding of the principles of thermodynamics and its classical applications. Also included are the applications of chemical engineering thermodynamics to issues such as the distribution of chemicals in the environment, safety, polymers, and solid-state-processing.
Ch. 1. Introduction -- Ch. 2. Conservation of Mass and Energy -- Ch. 3. Entropy: An Additional Balance Equation -- Ch. 4. The Thermodynamic Properties of Real Substances -- Ch. 5. Equilibrium and Stability in One-Component Systems -- Ch. 6. The Thermodynamics of Multicomponent Mixtures -- Ch. 7. The Estimation of the Gibbs Free Energy and Fugacity of a Component in a Mixture -- Ch. 8. Phase Equilibrium in Mixtures -- Ch. 9. Chemical Equilibrium and the Balance Equations for Chemically Reacting Systems -- App. I. Conversion Factors for SI Units -- App. II. The Molar Heat Capacities of Gases in the Ideal Gas (Zero Pressure) State -- App. III. The Thermodynamic Properties of Water and Steam -- App. IV. Enthalpies and Free Energies of Formation -- App. V. Heats of Combustion.
Includes bibliographical references and index.
Keywords: Thermodynamics; Chemical engineering